2020
DOI: 10.1093/mnras/staa094
|View full text |Cite
|
Sign up to set email alerts
|

xGASS: Robust quantification of asymmetries in global H i spectra and their relationship to environmental processes

Abstract: We present an analysis of asymmetries in global Hi spectra from the extended GALEX Arecibo SDSS Survey (xGASS), a stellar mass-selected and gas fraction-limited survey which is representative of the Hi properties of galaxies in the local Universe. We demonstrate that the asymmetry in a Hi spectrum is strongly linked to its signal-tonoise meaning that, contrary to what was done in previous works, asymmetry distributions for different samples cannot be compared at face value. We develop a method to account for n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 61 publications
18
80
1
Order By: Relevance
“…An explanation for the lower asymmetric fractions we find is that the majority of the spectra used in the published results have 10 < SNR < 50, hence their A flux are likely affected by the relatively lower SNRs and have a larger scatter compared with our values. Our trends of higher asymmetric fractions in denser environments is in agreement with the results from Watts et al (2020) for xGASS satellites and centrals, with satellites found to be more frequently asymmetric than centrals and similarly for isolated vs group centrals.…”
Section: Comparison With Published Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…An explanation for the lower asymmetric fractions we find is that the majority of the spectra used in the published results have 10 < SNR < 50, hence their A flux are likely affected by the relatively lower SNRs and have a larger scatter compared with our values. Our trends of higher asymmetric fractions in denser environments is in agreement with the results from Watts et al (2020) for xGASS satellites and centrals, with satellites found to be more frequently asymmetric than centrals and similarly for isolated vs group centrals.…”
Section: Comparison With Published Resultssupporting
confidence: 90%
“…Recent studies of single dish spectra of Virgo and Abell 1367 cluster galaxies considered A flux > 2σ or 3σ as likely produced by external, environmental influences and found asymmetric fractions of ∼ 16-26% (Scott et al 2018) and 27% for close galaxy pairs (Bok et al 2019) using the AMIGA sample 3σ significance threshold. Watts et al (2020) classified xGASS (Catinella et al 2018) galaxies as satellites or centrals and measured A flux , finding that satellites show a higher frequency of asymmetries than centrals, which supports the previous findings of asymmetries being more common in higher density environments. However, taking this further and understanding the physical origin of spectral asymmetries requires knowledge of the spatial distribution of gas within galaxies and the gas kinematics.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…For example, Richter & Sancisi (1994) found that half of the 1700 galaxies they studied showed a strong lopsidedness in their global H i profiles. A recent study by Watts et al (2020) of 562 galaxies finds a proportion of 37%. Espada et al (2011) studied lopsidedness in H i and distinguished between isolated and field galaxies.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, with ≈ 150-200 resolved galaxies out to z < 0.09, MIGHTEE-HI will provide a large homogeneous sample beyond the local Universe, which will significantly contribute to the above-mentioned studies. Additional information can be gained from the shape of the resolved H i spectral profile (Watts et al 2020).…”
Section: Kinematics From Spatially Resolved H Imentioning
confidence: 99%